Ubiquitous knowledge and experiences to foster EFL learning affordances. Issue 7 (2nd October 2016) - García-Sánchez, Soraya; Luján-García, Carmen
ABSTRACT: This article explores the implementation of experiential learning affordances to improve skills in English as a Foreign Language (EFL) in higher education. The administration of an online anonymous survey to 100 students of different undergraduate degrees presents current learning reflections from EFL students at the Universidad de Las Palmas de Gran Canaria (ULPGC, Spain) with regards to their active learning skills in their compulsory EFL course programmes. The findings demonstrate that students' motivation remains essential at the time of learning a foreign language. Equally, intrinsic motivation is linked to improving learners' communicative competence in English by means of using individual and interactive learning strategies, which at the same time participate in ubiquitous learning (u-learning) environments that happen anywhere and at any time in order to promote team activities outside the institutional times and places.